Addition to a checklist of the water mites of Turkey (Acari: Hydrachnidia) with description of two new species - Pešİ?, Vladimir; Erman, Orhan; Esen, Yunus (Institute for Biodiversity and Ecology, 2021)
In the publication of Erman et al. (2010), the depository for the holotypes of Atractides (Atractides) anatolicus Peši?, Erman & Esen sp. nov. and Atractides (Atractides) martini Peši?, Erman & Esen sp. nov., respectively, was not given. Therefore, the names of both species are invalid (International Code of Zoological Nomenclature 1999, Art. 16.4.2). We declare here that the holotype male of Atractides anatolicus and the holotype male of Atractides martini are deposited in the Naturalis Biodiversity Center in Leiden (RMNH). The purpose of this note is to validate the name of both new species (International Code of Zoological Nomenclature 1999, Art. 13.1.2). © 2021